Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set: 54

Answer

$-2b^{3}\sqrt (5a)$

Work Step by Step

$-\sqrt (20ab^{6})=-\sqrt (4\times 5a\times b^{6})=-(\sqrt 4\times \sqrt (5a)\times \sqrt (b^{6}))=-(2b^{3}\sqrt (5a))=-2b^{3}\sqrt (5a)$ We know that $\sqrt 4=2$, because $2^{2}=4$. We also know that $\sqrt (b^{6})=b^{3}$, because $(b^{3})^{2}=b^{3\times2}=b^{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.